Summary - Sturluson, Snorri (Scandinavistica Vilnensis, 2017)
Snorri Sturluson. Edda. Translated from Old Icelandic by Rasa Ruseckienė. (Edited by Ieva Steponavičiūtė Aleksiejūnienė). (Akademinė leidyba, 2017).This is an annotated translation of Snorri Sturluson’s mythopoetic treatise Edda (~1220) into Lithuanian. The book includes translator’s commentary, the introductory essay about Snorri Sturluson, his Edda and the Skalds, the index of proper names, place names and texts, and the bibliography.
Keywords: Snorri Sturluson; Edda; translation into Lithuanian; Old Norse literature